The impact of changes in dwelling characteristics and housing preferences on house price indices - Peter Reusens; Frank Vastmans; Sven Damen (National Bank of Belgium, 2022)
Hedonic house price indices adjust the average sales prices for the change in the quality of the property sold over time. This paper proposes a framework to disentangle the contribution of each individual dwelling characteristic to this quality change. We apply our framework to a unique dataset for Belgium for the period 2011Q3-2021Q2 in which we combine the universe of residential real estate transactions with the datasets of the energy performance certificates of the regional energy authorities. We find that the price of an identical dwelling has increased by 7 % less over the past decade compared to the average price of the houses sold and this is largely the result of the improved energy performance over the past decade. Moreover, taking into account the energy efficiency in house price indices will only become more important as it will need to improve substantially more to reach the European climate goal of having an energy efficient building stock by 2050. Turning to the recent period, we show that the strong price increases observed in the first year of the COVID-19 pandemic are not due to changes in the quality of the property sold as the average dwelling characteristics remained broadly stable. Furthermore, despite the slightly increased price discount of terraced houses and small garden and dwelling sizes, price growth continued to be slightly higher in cities compared to their rural urban fringe and the commuter belt.
Keywords: C43; E30; E31; Q58; R31; 330; House price index; hedonic regression; quality adjustment; housing market; COVID-19 pandemic; energy efficiency